Complications After Subpectoral and Prepectoral Tissue Expander Placement in Women Undergoing Postmastectomy Radiation Therapy - Seamus Caragher, MD, MPhil; Alisha Paranzino, MD; Stephen Stearns, MD; Libby Copeland-Halperin, MD; Jessica Erdmann-Sager, MD (Plastic and Reconstructive Surgery, Global Open, 2025)
Background:. Placement of tissue expanders is a critical tool in breast reconstruction, particularly with postmastectomy radiation. Prepectoral tissue expander placement has rapidly gained popularity. As such, the precise effects of tissue expander plane selection on outcomes following radiotherapy remain a key question. Methods:. All patients undergoing mastectomy and tissue expander placement followed by radiation at a single center between 2019 and 2021 were retrospectively examined. Clinical, oncological, surgical, and radiation treatment variables, as well as rate of complications before and after radiation, were collected. Multivariate analysis was performed. Results:. The 2 groups had similar baseline clinical and oncological characteristics. Prepectoral placement was more common in bilateral reconstruction and had smaller final tissue expander volume to mastectomy specimen weight ratio. There was no difference in the rate of postoperative or radiation complications based on tissue expander location (17% versus 18%). Multivariable analysis identified acellular dermal matrix as a significant protective factor against perioperative complications (odds ratio [OR]: 0.15; 95% confidence interval [CI]: 0.03–0.78). Increased age and the use of neoadjuvant chemotherapy were significant risk factors for radiation-related complications (age OR: 2.6; 95% CI: 1.02–6.63; Chemo OR: 16.7; 95% CI: 1.55–180). Conclusions:. Prepectoral tissue expander placement can be safely used with postmastectomy radiation. These results highlight acellular dermal matrix use as a major protective factor against complications in these patients. Independently, increased age and the use of neoadjuvant chemotherapy increased the risk of radiation-induced complications. The lack of significant risk with other variables can further assure surgeons of the safe use of prepectoral expanders in radiation-bound patients.